Association between Adverse Childhood Events (ACEs) and long-term COVID-19 symptoms: evidence from the 2022 behavioral risk factor surveillance system - Safa Elkefi; Alana Steffen; Alicia K. Matthews (BMC Public Health)
Abstract Objective This study investigated the association between Adverse Childhood Events (ACEs) and long-term COVID-19 symptoms. Methods We used data from the 2022 Behavioral Risk Factor Surveillance System. Multivariable logistic regression was used to assess the association between long-term COVID symptoms and ACEs, adjusting for demographic characteristics (race/ethnicity, age, and sex). Survey weights were applied. Results Of the 14,560 participants, 46.73% experienced 1–3 ACEs, and 26.81% experienced 4 + ACEs—23.38% experienced long-term COVID-19 symptoms. Blacks (OR = 0.76, P =.002) and Asians (OR = 0.56, P =.009) were less likely than Whites to experience long-term COVID-19, but American Indians (OR = 1.72) were more likely. Adults aged 35–69 had a higher likelihood of long-term symptoms than younger adults (OR = 1.24), whereas those aged 70 or older did not differ from younger adults. Females were also more likely to experience them (OR = 1.61). Exposure to ACEs was positively associated with long-term COVID-19 symptoms. The more adverse events individuals were exposed to, the more risk of long-term COVID-19. Specifically, experience of household substance abuse (OR = 1.14, 95%, P =.008), physical abuse (OR = 1.18, 95%, P =.001), emotional abuse (OR = 1.13, 95%, P =.014), sexual abuse (OR = 1.43, 95%, P <.001), and household mental illness (OR = 1.35, 95%, P <.001) were positively associated with the long-term COVID-19 experience. Conclusions Study findings contribute to the extensive literature demonstrating the negative health consequences of childhood adversities. More adverse events resulted in more risk to experience long term COVID-19 symptoms. Additional research is needed to better understand and intervene in the biological vulnerabilities associated with childhood adversities.